Pioneering advantages in manufacturing and service industries: empirical evidence from nine countries - Song, X. Michael; Benedetto, C. Anthony Di; Zhao, Yuzhen Lisa (Strategic Management Journal, 1999)
Although one might expect differences between manufacturing and service firms in pioneering advantages, the extent of these differences has not yet been investigated. This is the first cross-national study that compares such differences in nine countries/regions: the United States, the United Kingdom, Germany, Japan, China, Taiwan, Hong Kong, South Korea, and Singapore. We develop several hypotheses concerning the perceptions of managers of manufacturing firms and service firms regarding the benefits and post-entry risks of pioneering, and the cost and differentiation advantages accruing to the pioneering firm. We test the hypotheses with data from 2,419 firms representing all nine countries and both industrial sectors. We find that: (1) managers from all countries perceive pioneering to be associated with higher market share and/or profitability; (2) manufacturing firm managers perceive pioneering risks to be significantly more important than do service firm managers; (3) cost and differentiation advantages of pioneering are, for the most part, more significant to manufacturing than to service firm managers; (4) Western manufacturing firm managers perceive the cost advantages to be more important than Asian Pacific manufacturing firm managers. We conclude by presenting the managerial implications of our findings. Copyright © 1999 John Wiley & Sons, Ltd.